The Use of Balanced Scorecard in Assessing Public Service Performance - VRABIE Tincuța; CRISTACHE Nicoleta; NĂSTASE Marian (Applied Research in Administrative Sciences)
Performance evaluation plays an important role in any organization as an autonomous legal entity with material and human resources, which are needed to achieve its objectives. Since it is a management tool, in order to understand the process of performance evaluation, it is necessary to understand the methodological activities based on the stages, cases, principles, methods, techniques, procedures, and processes, and which are impacted by the behaviour of each member of that organization in order to ensure the achievement of the indicators set by managers, i.e. to guarantee performance. Implementing the Balance Scorecard in public services is important and must start from the challenge related to the performance level, posed to public service managers from the perspective of public service beneficiaries. Evidence has shown inefficient and even lack of transparency concerning the development strategy of a public service related to its beneficiaries. Therefore, the main focus of managers, regardless of their position in the organization, must be on the indicators which assess the degree of satisfaction of public service beneficiaries, employees, the range of procedures, processes, and the dynamics of results.